Risk assessment of fluoride daily intake from preference beverage - Ryouichi Satou; Sari Oka; Naoki Sugihara (Elsevier, 2021)
Background/purpose: Tea, coffee and alcohol beverages are called preference beverage and are drunk habitual and in large quantities. Therefore, there is a high possibility that a health risk is caused by the contained components, and risk assessment of intake is essential. However, the risk assessment of fluoride intake from preference beverages has not been sufficiently performed. Materials and methods: This study estimated the daily fluoride intake from preference beverages by measuring the fluoride concentration of infusion liquid and measuring the total fluoride content by the microdiffusion method. In addition, Hazard Quotient (HQ) was calculated for children and adults to assess the risk of fluoride intake. Results: As a result of this study, tea was the highest in all sample species, the infusion of tea was 1.06-6.68 mg/L and the total fluoride content of tea was 47.05-291.98 mg/kg. Green tea showed the next highest value, 0.26-4.09 mg/L, 21.91-83.68 mg/kg. Herbal tea fluoride levels were 0.07-0.17 mg/L and 0.05-1.90 mg/kg, Unique tea was 0.03-0.60 mg/L and 0.03-32.37 mg/kg, Coffee was 0.03-0.15 mg/L and 0.04-0.64 mg/kg. Conclusion: The HQ values calculated from the average daily fluoride intake (DFI) of preference beverages were all within the safe range. Some products made from Camellia sinensis, such as tea and green tea, had 1.66 mg/day as DFI at maximum, and the Child's HQ exceeded 1. These results suggest that habitual consumption of some products requires risk management of dental fluorosis.